A comparative study of hearing aids and round window application of the vibrant sound bridge (VSB) for patients with mixed or conductive hearing loss. (April 2013) - Marino, Roberta; Linton, Nicola; Eikelboom, Robert H.; Statham, Elle; Rajan, Gunesh P.
Abstract Objective: This study was undertaken to determine the efficacy of the round window (RW) application of the vibrant soundbridge (VSB) in patients with mixed or conductive hearing loss. Design: Speech in quiet and in noise were compared to preoperative data attained with conventional hearing aids so that each subject served as his or her own control in a single test protocol. Study sample: Eighteen adults implanted monaurally with the VSB in the poorer hearing ear. Experience with the VSB ranged from nine to 25 months. Results: Sixteen of the 18 subjects were successful VSB users, wearing their device all waking hours. There was no significant deterioration in the averaged bone conduction results preoperatively versus post-operatively (p > 0.05). Speech recognition in quiet results were not significantly different to performance attained whilst wearing hearing aids (p > 0.05). Speech recognition in noise performance was substantially improved with use of the VSB in most test conditions. Conclusions: For the majority of the subjects, the VSB was an effective method of hearing restoration for their mixed and conductive hearing loss.